Distribution, source, and ecological risks of polycyclic aromatic hydrocarbons in Lake Qinghai, China. (November 2020) - Cao, Yuanxin; Lin, Chunye; Zhang, Xuan; Liu, Xitao; He, Mengchang; Ouyang, Wei
Abstract: Contamination by polycyclic aromatic hydrocarbons (PAHs) has been observed at high elevation environments; however, the occurrence and spatial variation of PAHs in alpine lakes of China is not well understood. We measured 15 priority PAHs in the sediments of Lake Qinghai in the Qinghai-Tibet Plateau, and assessed their distribution, source, and ecological risks. The total PAH concentration ranged from 30.4 to 125.2 ng g −1 . Low molecular weight PAHs were dominant in the sediments, suggesting a local source for the emissions. Sediment sites closer to local settlements and rivers had higher concentration of PAHs. The concentration of PAHs was significantly correlated with pH, probably as a result of the high salinity of the lake, while it was not significantly correlated with organic matter content. Molecular diagnostic ratio analysis indicated that PAHs were derived mainly from coal and biomass combustion. Specifically, the positive matrix factorization model showed that petrogenic sources, vehicular emissions, biomass combustion, and coal combustion contributed for 11.6, 16.3, 23.6, and 48.5% of the PAHs, respectively. The risk quotient method was used to assess ecological risk of PAHs individually. The results indicate that indeno[1, 2, 3-cd]pyrene, benzo[b]fluoranthene, benzo[a]pyrene, phenanthrene, and anthracene would produce moderate ecological risks in 5, 20, 65, 100, and 100% of the sediment sites, respectively, while the other 10 PAH homologues would scarcely produce any serious ecological risk. We used the hierarchical Archimedean copula integral assessment model to evaluate the integral risk of PAHs. The result showed that 10, 40, and 50% of the sediment sites belong to mid-high, low, and mid-low risk levels, respectively. The current concentration and risk levels of PAHs in this study might be used as a baseline to assess the influence of future anthropogenic activities. Graphical abstract: Image 1 Highlights: Polycyclic aromatic hydrocarbons(PAHs) in Lake Qinghai mostly originated from coal and biomass combustion. Low molecular weight PAH dominance revealed the main source as local emissions. PAHs were significantly correlated with pH but not with organic matter in sediment. Low ecological risks were mainly from phenanthrene, anthracene and benzo[a]pyrene. PAHs in the lake can be used to develop their baselines in alpine lakes globally.